Rules governing the genetic code degeneracy/redundancy and spatial organization of the codon informative properties - Rapacioli, Melina; Katz, Ricardo; Flores, Vladimir (Frontiers in Applied Mathematics and Statistics, 2024)
The present work is devoted to describing the "logic" implicit in the standard genetic code. Bases are considered as physicochemical entities possessing two essential properties: molecular type and number of Hydrogen bonds involved (bases pairing) of the Codon-Anticodon specific interactions. It is proposed that the codon structure possesses a dual informative function: on the one hand it determines its discriminating or non-discriminating character and, on the other, it determines a specific amino acid. These two aspects constitute the codon global information. Two different set of rules are introduced to describe these different phenomena. It is established that, depending on the kind of base occupying the second position only two or three of the six codon properties located at defined positions determine the discriminating or non-discriminating behavior. With regards to the amino acid determining function of the codons, for different sets of synonymous (singlets, doublets, triplets, quadruplets, or sextets) the number of informative properties integrating the codon, and their typical positions characteristically change. Based on the rules here presented it can be postulated that a codon can be defined as an asymmetric informative entity, whose global informative capacity results from the spatially organized combinatory of the six properties assigned by the three bases.